Non-profit organizations in the Republic of Tuva from 2015 to 2021: Path dependence - Skobelina, Natalia A. (The New Research of Tuva, 2022)
Modifications in the institutional environment lead to radical transformations in the non-profit sector. In contemporary Russia, changes in formal rules have modified the trajectory of development, opened up new vistas and resources for non-profit organizations. The analysis of research literature, legislative acts of federal and regional authorities is based on the concepts of the neo-institutional theory. It allowed us to determine the development direction of socially oriented non-profit organizations (SO NPOs) in the Republic of Tuva from 2015 to 2021 in the all-Russian context. The study shows the institutional dependence of non-profit organizations on state policy (its path dependence). As shown by the results of the research, the main direction of development for SO NPOs in Tuva in recent years has been mainly related to the social sphere. Local authorities establish registers of non-profit organizations, provide financial and material assistance, the Head of Tuva supports social projects of NPOs. Non-profit organizations provide social services to various categories of citizens. They use new rehabilitation technologies, develop inclusive practices for people with disabilities.